(3GdJMHjQ aj GdJPcjQ (B( (3aj TQM CSeGA Gddg GdMSfi (B)s - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjSJaJM dg hLhO CeG HYO abO cKQ SDGd GdQGZHjf ai Yde GdJPcjQ s
(3BNQgG (B:s
(3hCeG eGjLH Ydi GdYHO ef GdUHQ agh GdUHQ Ydi eG CeQg Gddg Hg hbO GfJgi cJGHfG gPG hMSHi Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs